(untitled) (SAARC Journal of Agriculture, 2025)
A rice genotype’s stability and adaptability are necessary for its commercial adoption as a variety under a wide range of growing environments. This study aimed to evaluate the Genotype × Environment (GE) interaction and to find a stable rice genotype for varietal development. Utilizing additive main effects and multiplicative interaction (AMMI) and genotype main effect and genotype by environment interaction effects (GGE) analyses, three rice genotypes were studied for grain yield stability across seven environments. The GGE and AMMI studies showed strong GE interactions, showing variability in genotype and environment. The genotype RM-LD-1 was selected as the top performer for the trait, grain yield, according to AMMI1 and AMMI2 biplot models. The genotype RM-LD-1 had the highest yield and the most stability, according to a GGE biplot study (mean vs. stability). According to the genotype ranking graph, the genotype RM-LD-1 was determined as the best genotype for grain yield, followed by BAU-3 and BRRI dhan28. The genotype RM-LD-1 performed better in the environments Chapainawabganj, Rangpur, Sunamganj, and Mymensingh, according to the GGE biplot-polygon analysis. The genotype RM-LD-1 might be considered as a variety based on yield and wide environmental adaptation. SAARC J. Agric., 23(1): 123-137 (2025